Do remittances, foreign aid, and FDI serve as automatic output stabilizers in Sri Lanka? An application of the ARDL approach - Maheswaranathan, S.; Chesika, M. (University of Jaffna, 2024)
For developing nations in particular, the country has strong ties to Foreign Direct Investment (FDI), remittances, and official development assistance. Foreign capital receipts are crucial to Sri Lanka’s economic advancement, as with other developing nations. A thorough comprehension of the ramification of these overseas finance on Sri Lanka's national income growth is still lacking, despite much study in the field. This study strives to resolve that void by analyzing the effects of external inflows on Sri Lanka's Gross Domestic Product (GDP) from 1980 to 2022, utilizing available and reliable data. An Autoregressive Distributed Lag (ARDL) model enabled an analysis of the variables' relationship. According to this analysis, Sri Lanka's sustained economic growth is heavily depends by personal remittances, Official Development Assistance, and Foreign Direct Investment. In addition, the Error Correction Term's value of -0.776953 shows that a yearly adjustment of 77.69 will be made to any short-term aberrations in economic growth caused by external shocks, allowing for a restoration to long-term equilibrium. The high Error Correction Term (ECT) value shows that Sri Lanka's economy can withstand a lot of pressure from outside. Stronger financial systems, more diverse economies, and better institutions are the tenets of macroeconomic policies that can fortify this resilience. By providing actual data on the impact of monetary flows on Sri Lanka's growth, this study adds to the existing literature. The findings will provide valuable implementations for policymakers and scholars in enticing funding from outside sources.
Keywords: ARDL approach; Economic development; Foreign; Remittances; JEL Classification: B23